The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1108/09600030710825694
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral supply management: a taxonomy of judgment and decision‐making biases

Abstract: PurposeThe purpose of this paper is to review and integrate the extensive literature base which examines judgment and decision‐making biases, to introduce this literature to the field of supply management, to create a valid, mutually exclusive, and exhaustive taxonomy of decision biases that can affect supply managers, and to provide guidance for future research and applications of this taxonomy.Design/methodology/approachThe authors use a qualitative cluster analysis, combined with a Q‐sort methodology, to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
142
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(149 citation statements)
references
References 278 publications
1
142
0
2
Order By: Relevance
“…For example, availability and representativeness heuristics, in fact, constitute a single heuristic which Kahneman and Frederick (2002) called attribution substitution (however, the tradition to distinguish between the two stuck in both research and practice). Later, Krueger and Funder (2004) produced a list of the 42 most important cognitive biases from the perspective of psychological research, while Carter et al (2007) list 76 decision biases in business and management and divided them into nine categories.…”
Section: Variety Of Behavioral Biases and Their Causesmentioning
confidence: 99%
“…For example, availability and representativeness heuristics, in fact, constitute a single heuristic which Kahneman and Frederick (2002) called attribution substitution (however, the tradition to distinguish between the two stuck in both research and practice). Later, Krueger and Funder (2004) produced a list of the 42 most important cognitive biases from the perspective of psychological research, while Carter et al (2007) list 76 decision biases in business and management and divided them into nine categories.…”
Section: Variety Of Behavioral Biases and Their Causesmentioning
confidence: 99%
“…Most of the previous researchers in their experimental studies have considered long lead time (4 periods) and uniform distribution with a range of 0 to 8 or step-up demand pattern for the customer demand (Sterman, 1989;Croson & Donohue, 2003, Croson & Donohue, 2006, Wu & Katok, 2006; assuming a uniform customer demand is unusual (Steckel et al, 2004) and normal distribution is the best choice for the same (Chan & Chan, 2010). Carter et al (2007), Bendoly et al (2010), Tokar (2010), and Cantor and Katok (2012) highlighted the need for behavioural research in logistics and supply chain management in which human beings are used for conducting experiments. They concluded that the behavioural research in logistics and supply chain management can significantly advance both theory and practice in the logistics and supply chain management.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the new field of behavioral operations management has essentially transferred the approach of behavioral economics to the study of the management of operations such as supply chains (Katsikopoulos & Gigerenzer, 2013). This can be seen in how the field is defined as the study of biases (Carter, Kaufmann, & Michel, 2007), in the flurry of optimization models that are being developed (Loch & Wu, 2005) and in the neglect of the underlying psychological processes (Croson & Donohue, 2002). In the field of engineering design, pragmatic models have been received with furious anger by proponents of idealistic modeling who controlled funding in the United States National Science Foundation for years (see the response of Hazelrigg, 2010to Frey et al, 2009.…”
Section: The Story Told By the Idealistic Culturementioning
confidence: 99%